UV Assisted Enhanced Photodegradation of Carbaryl Pesticide with Ag Doped ZnO NPs - Satheesh, A.; Rao, J. C.; Ramanjaneyulu, M. V. V.; Jogayya, K. N.; Kalyan, K. V.; Kumar, A.; Usha, H. (Journal of Scientific Research, 2024)
Every year approximately one million tonnes of pesticide effluents are releasing into natural streams and water bodies from nearby industries and agricultural fields. It is necessary to remove pesticides and their residues from water bodies to protect environment and ecosystem. Photodegradation is an effective method to remove the organic contaminants from water bodies due to its low cost, environmental friendliness and absence of secondary pollutants. This work presents about the synthesis, characterization of pure and silver doped ZnO nanoparticles (NPs) and their efficiency towards the photo degradation of carbaryl pesticide. Pure and Ag doped nanoZnO particles were synthesized by wet chemical method using zinc nitrate as precursor and the synthesized nano particles were studied using FT-IR, XRD, UV-Vis, SEM, EDAX, TEM and fluorescence spectral analysis to evaluate its structural, morphological, optical and fluorescent properties. Carbaryl pesticide was taken at a fixed concentration of 5 ppm, and subjected to photo degradation by adding 5 mg/L of pure and Ag doped nanoZnO separately under UV irradiation. It is observed that in 60 min 90 % of the pesticide was degraded with pure ZnO NPs and 98 % with Ag doped ZnO NPs.